INFRA-TRADE NET WORKS, SOCIAL PROMOTION STRATEGIES AND LEGAL STATEMENTS. MAGELLAN , 1899. - Boric Bargetto, Ljuba (Revista de Historia Social y de las Mentalidades, 2016)
From the micro-historical study of a court case  corresponding to a theft executed by inmigrant  Croatian Juan Spanich in Punta Arenas in 1899,  it is intended to mean and valuate those aspects  that can contribute to the reconstruction and  questioning of an immigration society, and thus  present the gap existing in relation to judicial  topics in the current historiography regarding  migration studies. In this sense, this article will show the  development of networks of infra- trade and  solidarity networks as recurring practices by  immigrants in a society of emerging business  growth, marked by credit systems, bonds and  social promotion mechanisms, i.e. cultural  elements as the " honor", "respect" and "public  fame," which transcended spheres of social and  articulated as symbolic discourses in judicial  contexts.
Keywords: Solidarity networks; Inmigrants; Judicial discourses